2010
DOI: 10.1085/jgp.200910302
|View full text |Cite
|
Sign up to set email alerts
|

Carotid body chemosensory responses in mice deficient of TASK channels

Abstract: Background K+ channels of the TASK family are believed to participate in sensory transduction by chemoreceptor (glomus) cells of the carotid body (CB). However, studies on the systemic CB-mediated ventilatory response to hypoxia and hypercapnia in TASK1- and/or TASK3-deficient mice have yielded conflicting results. We have characterized the glomus cell phenotype of TASK-null mice and studied the responses of individual cells to hypoxia and other chemical stimuli. CB morphology and glomus cell size were normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
89
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 68 publications
(117 reference statements)
9
89
0
Order By: Relevance
“…In the study by Wyatt et al (2007) it was also shown that the AMPK antagonist compound C reversed the just described effects of hypoxia and AICAR on chemoreceptor cells. Although ironically, from a cynic point of view, it might be said that most of the effects seen on AMPK activation and inhibition are epiphenomenal to O 2 -sensing, because maxiK inhibition (Gomez-Niño et al, 2009a,b) and genetic elimination of TASK-1 and TASK-3 do not affect hypoxic behaviour of chemoreceptor cells (Ortega-Sáenz et al, 2010). It must be unambiguously stated that the data generated by Wyatt et al (2007) would indicate that AMPK dependent phosphorylation of K + channels in CB chemoreceptor cells mimic hypoxia and appears capable of eliciting integrated CB afferent activity, arguing in the favour that AMPK activation is a key element in the hypoxic transduction cascade.…”
Section: Bioenergetic O 2 Sensorsmentioning
confidence: 99%
“…In the study by Wyatt et al (2007) it was also shown that the AMPK antagonist compound C reversed the just described effects of hypoxia and AICAR on chemoreceptor cells. Although ironically, from a cynic point of view, it might be said that most of the effects seen on AMPK activation and inhibition are epiphenomenal to O 2 -sensing, because maxiK inhibition (Gomez-Niño et al, 2009a,b) and genetic elimination of TASK-1 and TASK-3 do not affect hypoxic behaviour of chemoreceptor cells (Ortega-Sáenz et al, 2010). It must be unambiguously stated that the data generated by Wyatt et al (2007) would indicate that AMPK dependent phosphorylation of K + channels in CB chemoreceptor cells mimic hypoxia and appears capable of eliciting integrated CB afferent activity, arguing in the favour that AMPK activation is a key element in the hypoxic transduction cascade.…”
Section: Bioenergetic O 2 Sensorsmentioning
confidence: 99%
“…The TASK-3 channel is also overexpressed in a variety of cancers and confers hypoxia resistance on tumors (Mu et al, 2003). Knockout mice lacking one or both TASK channels display a variety of phenotypes, including impaired carotid body chemosensing (Ortega-Saenz et al, 2010), sleep fragmentation (Pang et al, 2009), antidepressive behavior (Gotter et al, 2011), primary hyperaldosteronism and low-renin essential hypertension (Davies et al, 2008;Guagliardo et al, 2012), and cardiac conduction and repolarization abnormalities Donner et al, 2011;Petric et al, 2012). An inactivating mutation in the human TASK-3 channel pore (G236R) is associated with the BirkBarel syndrome of mental retardation, hypotonia, and facial dysmorphism (Barel et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although this model of sensory transduction has been demonstrated in several animal models, it has not been studied in human tissues. We have prepared slices of human CB, to measure the secretory responses to hypoxia by amperometry, as well as dispersed CB cells to monitor the changes of cytosolic [Ca 2+ ] by microfl uorimetry (Garcia-Fernandez et al 2007 ;Ortega-Saenz et al 2010 ;Pardal et al 2000 ;Urena et al 1994 ). Representative recordings of catecholamine release from individual glomus cells subjected to low O 2 tension (PO 2 , ≈15 mmHg) and high (40 mM) potassium are illustrated in Fig.…”
Section: Cellular Responses To Hypoxiamentioning
confidence: 99%